Nanoparticles can wrap epithelial cell membranes and relocate them across the epithelial cell layer - Urbančič, I; Garvas, M; Kokot, B; Majaron, H; Umek, P; Cassidy, H; Škarabot, M; Schneider, F; Galiani, S; Arsov, Z; Koklic, T; Matallanas, D; et al. (American Chemical Society, 2018)
Although the link between the inhalation of nanoparticles and cardiovascular disease is well established, the causal pathway between nanoparticle exposure and increased activity of blood coagulation factors remains unexplained. To initiate coagulation tissue factor bearing epithelial cell membranes should be exposed to blood, on the other side of the less than a micrometre thin air-blood barrier. For the inhaled nanoparticles to promote coagulation, they need to bind lung epithelial-cell membrane parts and relocate them into the blood. To assess this hypothesis, we use advanced microscopy and spectroscopy techniques to show that the nanoparticles wrap themselves with epithelial-cell membranes, leading to the membrane's disruption. The membrane-wrapped nanoparticles are then observed to freely diffuse across the damaged epithelial cell layer relocating epithelial cell membrane parts over the epithelial layer. Proteomic analysis of the protein content in the nanoparticles wraps/corona finally reveals the presence of the coagulation-initiating factors, supporting the proposed causal link between the inhalation of nanoparticles and cardiovascular disease.